Temperature and Concentration Effects on Oscillatory Flow for Variable Viscosity Carreau Fluid through an Inclined Porous Channel - Al-Khafajy, Dheia G. Salih; Labban, Jubran Abdulameer (Iraqi Journal of Science, 2021)
The aim of this paper is to study the combined effects of the concentration and the thermo-diffusion on the unsteady oscillation flow of an incompressible Carreau fluid through an inclined porous channel. The temperature is assumed to affect exponentially the fluid’s viscosity. We studied fluid flow in an inclined channel under the non-slip condition at the wall. We used the perturbation series method to solve the nonlinear partial differential equations. Numerical results were obtained for velocity distribution, and through the graphs, it was found that the velocity of fluid has a direct relation with Soret number, Peclet number, and Grashof number, while it has a reverse variation with chemical reaction, Schmidt number, frequency of oscillation, and Froude number.